The contributions of public participation in environmental impact assessment (EIA) towards promoting sustainable development in Malaysia - Ramli, Rosnadhirah; Mohamed, Mohd Zin; Zahari, Rustam Khairi (2012)
Public participation in the planning process is very important due to the fact that the public has the right to live in a healthy environment and the obligation to protect the environment. Generally, Malaysia started the Environmental Impact Assessment (EIA) in 1988 as a mandatory legislative requirement to protect and enhance the quality of the environment. EIA was introduced to measure the benefit or cost from physical development to the public. To promote the active participation from the public in achieving better decisions on environmental effects, all parties shall cooperate in taking appropriate actions. While promoting the public participation in the EIA as one of the means in contributing to the sustainable development, this research also aimed at discussing the strategies that can be adopted in order to enhance the participation and involvement of the public. High participation from the public leads to a comprehensive and better decision making. Therefore, the strategies recommended in this research are hoped to improve the public participation generally in the planning process and specifically in the EIA towards realizing the green city through the implementation of sustainable development project.